1998
DOI: 10.1046/j.1432-1327.1998.2580419.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning, in vitro expression, and biochemical characterization of cholinesterase 1 and cholinesterase 2 from amphioxus

Abstract: We have isolated cDNAs coding for the complete amino acid sequences of cholinesterase 1 (ChE1) and cholinesterase 2 (ChE2) from amphioxus. Both ChE transcripts have the characteristics of H-type catalytic subunits, which are inserted in the membrane via an ethanolamine-glycan-phosphatidylinositol anchor. The members of the catalytic triad of ChEs, the three pairs of cysteine residues involved in intrachain disulfide bonding, a cysteine near the carboxy terminal of both sequences, which could mediate interchain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…is the closest living invertebrate relative of the vertebrates (Satoh et al 2001). Previously, we found that amphioxus (Branchiostoma lanceolatum and Branchiostoma floridae) possesses two AChEs, which we call ChE1 and ChE2 to distinguish them from the AChE of the vertebrates (Sutherland et al 1997;McClellan et al 1998;Pezzementi et al 1998). Interestingly, ChE2 has two free cysteines in the catalytic gorge: one in the vicinity of the acyl pocket, Cys310, which is homologous to the free cysteine in aphids and mosquitoes; and another, Cys466, which is adjacent to the choline-binding site.…”
Section: Introductionmentioning
confidence: 99%
“…is the closest living invertebrate relative of the vertebrates (Satoh et al 2001). Previously, we found that amphioxus (Branchiostoma lanceolatum and Branchiostoma floridae) possesses two AChEs, which we call ChE1 and ChE2 to distinguish them from the AChE of the vertebrates (Sutherland et al 1997;McClellan et al 1998;Pezzementi et al 1998). Interestingly, ChE2 has two free cysteines in the catalytic gorge: one in the vicinity of the acyl pocket, Cys310, which is homologous to the free cysteine in aphids and mosquitoes; and another, Cys466, which is adjacent to the choline-binding site.…”
Section: Introductionmentioning
confidence: 99%
“…predicted protein with 25% identity and 31% similarity to ColQ from T. marmorata (NCBI Reference Sequence: XP_798050.2; Tu et al, 2012). Likewise, there is also no evidence for the presence of asymmetric forms of ChEs in acraniate deuterostomes or in protostomes, with the possible exception of the cephalochordate B. floridae (McClellan et al, 1998). However, it has recently been found that soluble ChEs are evidently assembled by PRAD fragments derived from a variety of proline-rich intracellular proteins (Li et al, 2008;Biberoglu et al, 2012Biberoglu et al, , 2013, apparently via WAT-PRAD interactions (Larson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In amphioxus (Branchiostoma floridae), a cephalochordate, six putative ChE genes are present (Johnson and Moore, 2012a). cDNAs for two of these ChEs have been characterized: ChE1 is an atypical ChE, and ChE2 resembles the AChE of protostomes (Sutherland et al, 1997;McClellan et al, 1998;Pezzementi et al, 2003), the other major lineage of bilaterian animals (Lowe, 2008). A number of the other putative amphioxus ChEs genes have sequence characteristics typical of craniate AChE.…”
Section: Introductionmentioning
confidence: 99%
“…has two AChEs, cholinesterase 1 (ChE1) and cholinesterase 2 (ChE2) (McClellan et al, 1998). ChE2 has two free cysteines in the catalytic gorge: one in the acyl pocket near the top of the catalytic gorge, Cys310, homologous to the free cysteine in aphids and mosquitoes; and another, Cys466, adjacent to the choline-binding site near the bottom of the gorge.…”
Section: Introductionmentioning
confidence: 99%